2018
DOI: 10.1186/s12887-018-1236-2
|View full text |Cite
|
Sign up to set email alerts
|

The cut-off levels of procalcitonin and C-reactive protein and the kinetics of mean platelet volume in preterm neonates with sepsis

Abstract: BackgroundSepsis is a leading cause of morbidity and mortality among newborns. C-reactive protein (CRP) and procalcitonin (PCT) have some limitations in the diagnosis of preterm neonatal sepsis. In this study, the cut-offs of PCT and CRP, and the efficacy of mean platelet volume (MPV) were investigated.MethodsWe identified key demographic details and compared laboratory values between preterm infants with early onset and late onset neonatal sepsis (EONS/LONS) retrospectively. Blood samples were collected withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0
3

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 30 publications
3
21
0
3
Order By: Relevance
“…At this cut-off, the sensitivity, specificity, PPV, and NPV were 76.5%, 98.2%, 94.9%, and 90.5%, respectively. For the diagnosis of clinical sepsis, with CRP cut-off of 2.6 mg/L, the sensitivity, specificity, PPV, and NPV were 73.6%, 83.0%, 67.2%, and 86.9% respectively 26. In our study, we found the cut-off values of CRP in suspected EOS and proven EOS 4.5, 7.2 mg/L, respectively.…”
Section: Discussionsupporting
confidence: 47%
“…At this cut-off, the sensitivity, specificity, PPV, and NPV were 76.5%, 98.2%, 94.9%, and 90.5%, respectively. For the diagnosis of clinical sepsis, with CRP cut-off of 2.6 mg/L, the sensitivity, specificity, PPV, and NPV were 73.6%, 83.0%, 67.2%, and 86.9% respectively 26. In our study, we found the cut-off values of CRP in suspected EOS and proven EOS 4.5, 7.2 mg/L, respectively.…”
Section: Discussionsupporting
confidence: 47%
“…La incidencia de proporción entre los que desarrollaron sepsis fue de 0,44 (24/33) con una significancia estadística dada por un valor de p 0,000 (Tabla 4). Se utilizó para este análisis un valor positivo ≥ 10 mg/L; referenciando que es el valor óptimo con mayor utilidad diagnóstica según la literatura médica actual 21 . El riesgo relativo (RR) para los pacientes con PCR inicial elevada fue de 7,062 (IC 95% 3,5-14,2).…”
Section: Información Materna Control Prenatal Y Atención Del Partounclassified
“…In newborns, the source of the pathogen may be an in utero infection, maternal flora infection or postpartum infection from the hospital or community ( 2 ). Neonatal sepsis (NS) is a leading cause of morbidity and mortality in newborns ( 3 ), and it may be categorized as early-onset NS (EOS) or late-onset NS (LOS) ( 4 ). The morbidity and mortality of NS have been reduced due to progress made in neonatal care ( 5 ).…”
Section: Introductionmentioning
confidence: 99%